Profile of newborns with gastroschisis diagnosis in a public hospital at Porto Alegre(RS) - de Souza, Greice Kelli Coelho; Strapasson, Márcia Rejane; Fronza, Edegar; Ramos, José Geraldo Lopes (Clinical and Biomedical Research, 2017)
Objective: To know the profile of newborn diagnosed with gastroschisis and treated at a public hospital at Porto Alegre, southern Brazil. Method: A cross-sectional, descriptive, quantitative study was conducted to retrospectively analyze 54 medical records of neonates diagnosed with gastroschisis treated at the study hospital between January 2006 and January 2016. The analysis included all medical records of infants diagnosed with gastroschisis and born in the institution studied, as well as those who were transferred from other health institutions in the period examined. Medical records were searched through electronic consultation to the institution's Epidemiology Service, using the International Code of Diseases (ICD) 10 Q 793). Later, the files were accessed through the Medical Records and Statistics Service. Information was collected using a form containing the study variables. The data analysis was performed using SPSS software, version 21.0. The study complied with the ethical aspects of human research legislation. Results: The prevalence of gastroschisis was 0.11%, totaling 54 cases identified. Mean maternal age was 20.2 years; sex distribution was equal among newborns with the malformation; and 72.5% of cases had primary abdominal closure. Conclusion: The results for related causes and treatment, such as maternal age, drug use, and type of abdominal closure, were similar to findings from other studies on gastroschisis. Keywords: Congenital anomalies; gastroschisis; nursing care; neonatal nursing.